2021
DOI: 10.35812/cellulosechemtechnol.2021.55.48
|View full text |Cite
|
Sign up to set email alerts
|

"Stingless Bee Honey Incorporated Cellulose Hydrogel/Poly(lactic-Co-Glycolic Acid) Patch as an Alternative Treatment for Aphthous Stomatitis

Abstract: Aphthous stomatitis is a disease that often reappears, causing irritation and pain. Common topical medications to treat aphthous stomatitis are fast-dissolving synthetic drugs, sometimes with limited therapeutic effectiveness. In this study, a patch, composed of a stingless bee honey incorporated cellulose hydrogel layer and a poly(lactic-co-glycolic acid) (PLGA) layer, was fabricated as an alternative treatment for aphthous stomatitis. The composition of the honey patches was verified by the presence of a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On the other hand, Hegde et al (2017) reported that out of the 72 patients with recurrent aphthous stomatitis, 54.7% were females (36) . Also, in Abdullah et al (2013) study, out of 282 RAS was ++ more common among females 176 (62.4%) and males 106 (37.58%) with (p<0.004) (37) .Lo et al (2021) study also revealed higher percentage among females (55.4%) (38) .…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, Hegde et al (2017) reported that out of the 72 patients with recurrent aphthous stomatitis, 54.7% were females (36) . Also, in Abdullah et al (2013) study, out of 282 RAS was ++ more common among females 176 (62.4%) and males 106 (37.58%) with (p<0.004) (37) .Lo et al (2021) study also revealed higher percentage among females (55.4%) (38) .…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, the PLGA polymer released the honey into the extracellular matrix and rapidly closed the wound gap. In vivo analysis also demonstrated that the honey patches could inhibit the growth of E. coli in the first 2 h, followed by the inhibition of S. aureus in the next 2 h [84].…”
Section: Application Of Honey-based Hydrogel For Wound Healingmentioning
confidence: 91%
“…In vivo analysis also demonstrated that the honey patches could inhibit the growth of E . coli in the first 2 h, followed by the inhibition of S. aureus in the next 2 h [ 84 ].…”
Section: Application Of Honey-based Hydrogel For Wound Healingmentioning
confidence: 99%